Long‐term multicentre experience of adjuvant radiotherapy for pN3 squamous cell carcinoma of the penis. (27th December 2020) - Ager, Michael; Njoku, Kelechi; Serra, Maria; Robinson, Angus; Pickering, Lisa; Afshar, Mehran; Vyas, Lona; Eardley, Ian; Kayes, Oliver; Elmamoun, Mamoun; Khoo, Vincent; Ayres, Benjamin; et al.
Abstract : Objective: To present the long‐term adjuvant radiotherapy outcomes of patients with pN3 squamous cell carcinoma of the penis (SCCp) treated at two UK centres. Patients and Methods: We conducted a retrospective audit of all pN3 SCCp patients, deemed suitable for adjuvant therapy by a specialist multidisciplinary team at St George's and Leeds Hospitals, who received adjuvant radiotherapy. Primary outcomes were recurrence‐free survival (RFS), cancer‐specific survival (CSS) and overall survival (OS). Secondary outcomes were time to adjuvant treatment, frequency of in‐field recurrence, site and side of recurrence, and dose and schedule of radiotherapy. Results: A total of 146 patients were included: 121 completed radiotherapy, 4 did not complete radiotherapy and 21 did not start it. The median (interquartile range [IQR]) age was 59 (54–70)years. The 5‐year RFS was 51%, CSS was 51% and OS was 44%. Adjuvant radiotherapy was started at a median (IQR) of 75 (48–106) days. A dose of 45 Gy in 20 fractions was most commonly used. Of the 125 patients who started adjuvant treatment, 55 relapsed. Of these relapses, 30 occurred in an inguinal or pelvic nodal station and 26 of the 30 were in a radiation field. Relapses in 18 of the 55 cases were in visceral sites only and seven were in both nodal (non‐irradiated sites) and visceral sites. Doses of <50 Gy were used more commonly before 2013 and higher doses (>50 Gy) were more commonly used after 2013. Conclusions: Application of a standard radiotherapy protocol within a centralized supra‐network setting has achieved survival outcomes that would appear better than those previously documented for either radiotherapy or chemotherapy in a cohort with solely pN3 disease. The addition of adjuvant chemotherapy may improve these outcomes further. These data suggest that adjuvant radiotherapy has a role to play in the management of men with pN3 SCCp.